2018
DOI: 10.1007/s00774-018-0936-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of strontium and barium in the developing and mature skeleton of rats

Abstract: Bone acts as a reservoir for many trace elements. Understanding the extent and pattern of elemental accumulation in the skeleton is important from diagnostic, therapeutic, and toxicological perspectives. Some elements are simply adsorbed to bone surfaces by electric force and are buried under bone mineral, while others can replace calcium atoms in the hydroxyapatite structure. In this article, we investigated the extent and pattern of skeletal uptake of barium and strontium in two different age groups, growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…This is consistent with experimental work showing that barium from ingested liquids is rapidly incorporated into hydroxyapatite, and cleared from the bloodstream within a day of dosing. [ 34 ] Thus, sustained decreases of Ba/Ca in tooth enamel are likely to correspond to the withdrawal of enriched milk‐products or the cessation of nursing within days of the actual event.…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with experimental work showing that barium from ingested liquids is rapidly incorporated into hydroxyapatite, and cleared from the bloodstream within a day of dosing. [ 34 ] Thus, sustained decreases of Ba/Ca in tooth enamel are likely to correspond to the withdrawal of enriched milk‐products or the cessation of nursing within days of the actual event.…”
Section: Main Textmentioning
confidence: 99%
“…Figure 3D also shows a Sr/Ca transition at the end of artificial formula consumption, but it is slightly less defined compared to Ba and Pb, an observation that may reflect a more diffuse or delayed mineralization process for Sr, or longer retention in the bloodstream than Ba. [ 34 ] A study of postnatal Sr/Ca bands in an orangutan canine also found only a minor amount of elemental modification after initial secretion of the enamel and dentine. [ 23 ] These authors suggested that Sr overprinting may occur for approximately 1 to 2 months in each tissue, although the outermost enamel showed prolonged changes in Sr values that were not numerically quantified.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, alkaline earth metal ions such as barium and strontium exhibit high binding affinities to hydroxyapatite (HAP), resulting in an increased bone mineral density and an improvement in bone strength. It has been demonstrated that both barium and strontium target to bone where active bone formation and bone remodeling are taking place; this has been elucidated using 3D synchrotron K-edge subtraction micro-CT imaging ( Panahifar et al, 2018 ). Barium is highly toxic to the cardiovascular system due to potassium channel blockade, thus it is highly unlikely to be developed as a therapeutic bone-seeking agent ( Bhoelan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%